2008
DOI: 10.1152/japplphysiol.90727.2008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of active laryngeal closure during noninvasive intermittent positive pressure ventilation in nonsedated lambs

Abstract: The present study stems from our recent demonstration (Moreau-Bussiere F, Samson N, St-Hilaire M, Reix P, Lafond JR, Nsegbe E, Praud JP. J Appl Physiol 102: 2149-2157, 2007) that a progressive increase in nasal intermittent positive pressure ventilation (nIPPV) leads to active glottal closure in nonsedated, newborn lambs. The aim of the study was to determine whether the mechanisms involved in this glottal narrowing during nIPPV originate from upper airway receptors and/or from bronchopulmonary receptors. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 23 publications
(31 reference statements)
3
28
0
Order By: Relevance
“…Over the past decade, we have shown in several studies that an active inspiratory narrowing develops against ventilator insufflations during nPSV (15/4 cmH 2 O) in at least two thirds of full-term lambs in quiet sleep and quiet wakefulness (Moreau-Bussière et al, 2007;Roy et al, 2008). These results are in keeping with a recent review suggesting that this active inspiratory laryngeal narrowing can be responsible for significant patient-ventilator asynchrony, patient discomfort and non-invasive ventilation failure.…”
Section: 1-inspiratory Laryngeal Narrowing During Npsvsupporting
confidence: 85%
See 4 more Smart Citations
“…Over the past decade, we have shown in several studies that an active inspiratory narrowing develops against ventilator insufflations during nPSV (15/4 cmH 2 O) in at least two thirds of full-term lambs in quiet sleep and quiet wakefulness (Moreau-Bussière et al, 2007;Roy et al, 2008). These results are in keeping with a recent review suggesting that this active inspiratory laryngeal narrowing can be responsible for significant patient-ventilator asynchrony, patient discomfort and non-invasive ventilation failure.…”
Section: 1-inspiratory Laryngeal Narrowing During Npsvsupporting
confidence: 85%
“…This inspiratory laryngeal narrowing can have deleterious consequences, including limitation of lung ventilation (Oppersma et al, 2013) as well as diversion of the insufflated gas into the esophagus. We further showed that this inspiratory laryngeal narrowing during nPSV was reflexively driven by the stimulation of unidentified bronchopulmonary receptors (Roy et al, 2008).…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations